Structure, sensing and photocatalytic properties of two multifunctional 3D luminescent coordination polymers based on an N-heterocyclic carboxylic acid. (30th April 2018) - Zong, Ziao; Bi, Caifeng; Zhu, Zheng; Fan, Chuanbin; Meng, Xiangmin; Zhang, Xia; Fan, Yuhua
Abstract : Two novel luminescent coordination polymers, {[Zn(tmlb)(H2 tmlb)]·H2 O} n (1 ) and [Zn(tmlb)(bbibp)] n (2 ) ((bbibp = bis(benzoimidazo-1-ly)biphenyl), H2 tmlb = (1 H -1, 2, 4-triazol-1-yl)methylenebis(benzoic acid)), have been rationally designed and successfully solvothermally synthesized. Abstract : Two novel luminescent coordination polymers, namely, {[Zn(tmlb)(H2 tmlb)]·H2 O} n (1 ) and [Zn(tmlb)(bbibp)] n (2 ) ((bbibp = bis(benzoimidazo-1-ly)biphenyl), H2 tmlb = (1 H -1, 2, 4-triazol-1-yl)methylenebis(benzoic acid)), have been rationally designed and successfully solvothermally synthesized. Complexes1 and2 have been characterized by elemental analysis, IR spectroscopy, single-crystal X-ray diffraction, thermogravimetric (TG) analysis and powder X-ray diffraction (PXRD). Complex1 possesses a 2-fold interpenetrating 3-connected 3D framework with a point symbol of (6 3 ) topology. Complex2 exhibits a two-fold interpenetrating uninodal 4-connected 3D framework with a (6 5 ·8) topology. The luminescence studies reveal that complexes1 and2 display highly sensitive and selective luminescent sensing towards Cr(vi ) (CrO4 2− and Cr2 O7 2− ) anions, and complex2 displays highly sensitive and selective luminescence sensing towards Fe(iii ) cations. In addition, photocatalytic studies show that complex1 could be a good candidate for the photocatalytic degradation of methylene blue (MB), and complex2 could be a good candidate for the photocatalytic degradation of methylene violet (MV) and Rhodamine B (RhB).